Interactions of Adiponectin and Lipopolysaccharide from Porphyromonas gingivalis on Human Oral Epithelial Cells - Kraus, Dominik; Winter, Jochen; Jepsen, Søren; Jäger, Andreas; Meyer, Rainer; Deschner, James (PLOS ONE, 2012)
Background Periodontitis is an inflammatory disease caused by pathogenic microorganisms, such as Porphyromonas gingivalis, and characterized by the destruction of the periodontium. Obese individuals have an increased risk for periodontitis and show decreased serum levels of adiponectin. This in-vitro study was established to examine whether adiponectin modulates critical effects of lipopolysaccharide (LPS) from P. gingivalis on oral epithelial cells (OECs). Methodology/Principal Findings The presence of adiponectin and its receptors in human gingival tissue samples and OECs was analyzed by immunohistochemistry and PCR. Furthermore, OECs were treated with LPS and/or adiponectin for up to 72 h, and the gene expression and protein synthesis of pro- and anti-inflammatory mediators, matrix metalloproteinases (MMPs) and growth factors were analyzed by real-time PCR and ELISA. Additionally, cell proliferation, differentiation and in-vitro wound healing were studied. The nuclear translocation of NFκB was investigated by immunofluorescence. Gingival tissue sections showed a strong synthesis of adiponectin and its receptors in the epithelial layer. In cell cultures, LPS induced a significant up-regulation of interleukin (IL) 1β, IL6, IL8, MMP1 and MMP3. Adiponectin abrogated significantly the stimulatory effects of LPS on these molecules. Similarly, adiponectin inhibited significantly the LPS-induced decrease in cell viability and increase in cell proliferation and differentiation. Adiponectin led to a time-dependent induction of the anti-inflammatory mediators IL10 and heme oxygenase 1, and blocked the LPS-stimulated NFκB nuclear translocation. Conclusions/Significance Adiponectin may counteract critical actions of P. gingivalis on oral epithelial cells. Low levels of adiponectin, as observed in obese individuals, may increase the risk for periodontal inflammation and destruction.